ELECTRICAL EXCITATION OF SKELETAL MUSCLES FOR THE ESTIMATION OF TIME SINCE DEATH USING SQUARE WAVE GENERATOR - Jaybhaye, Prasad; Ghuge, Minakshi; Patil, Dnyanesh; Potdar, Ashutosh (Journal of Forensic Medicine and Toxicology, 2025)
Post-mortem electrical excitation of skeletal muscles was measured using needle electrodes inserted into human muscles. The electrical excitability of the orbicularis oculi and orbicularis oris muscles was evaluated in 19 cadavers using a subjective grading system developed by Krause and Popwassilew. Electrical stimulation was provided by a square wave generator producing constant-current rectangular impulses of 30 mA, 10 ms duration, and a repetition rate of 50 per second. It was observed that there was a significant negative correlation between the degree of muscle contraction and the post mortem interval. Rapid loss of muscle excitation was observed in cases where muscles were grossly damaged. Prolonged excitation was seen in cases where hematoma or emphysema of the eye was present.